Degradation of wheat straw/polylactic acid composites with and without sodium alginate in natural soil and the effects on soil microorganisms. Issue 6 (2nd December 2022) - Chai, Xicun; He, Chunxia; Liu, Yutao; Niyitanga, Evode; Wang, Luyang; Zhang, Weixing
Abstract: In order to improve the degradability of polylactic acid (PLA) composites and screen PLA degradation microorganisms. Sodium alginate was added into the wheat straw/PLA composites, and both composites (with/without sodium alginate) were buried in natural soil for 100 consecutive days subsequently. Weight loss and characterization of the PLA composites, carbon and nitrogen content in soil and microbial community composition were detected after degradation, with the result that the degradability of the PLA composites was greatly improved after the addition of sodium alginate. The weight loss of PLA composites with sodium alginate was 8.5%, which was 1.81 times that of PLA composites without sodium alginate. Sodium alginate and/or wheat straw in the PLA composites took the lead in the beginning course of the degradation. The added sodium alginate serves the purpose of making it easier to degrade the crystallization zone of the PLA composites. Bionectriaceae in the soil shoots up in the number after degradation, signifying its potential to be part of the microorganism family serving to degrade PLA composites. The results would help reveal the degradation mechanism of PLA composites and provide support for the screening of PLA composites degradation microorganisms. Abstract :